Monitoring Microplastic Release from Simulated Paddy Fields in Controlled Planting Containers - Rahmawati, Sari; Haribowo, Riyanto; Prayogo, Tri Budi (Jurnal Teknik Pengairan: Journal of Water Resources Engineering, 2025)
Slow-release fertilizer (SRF) has become widespread in agricultural practices to reduce nutrient leaching, but the fertilizer coating has the potential to pollute the environment. Microplastics from fertilizer coatings can be released from paddy fields, enter drainage channels, and pollute rivers and the sea. This study uses paddy field modeling in planting containers to measure microplastic mass concentration and release pattern for 10 days from paddy fields under controlled conditions. This planting container was designed to resemble a paddy field equipped with soil, rice plants, and an artificial drainage system. A total of 81 mg of microplastics from the fertilizer coating was put into the planting container, and every day water samples passing through the hole were collected and analyzed in the laboratory to obtain the mass and pattern of gradual changes in microplastic concentration. The results showed that the highest microplastic release occurred on day 1 at 19.000 mg/L and the lowest at a concentration of 0.500 mg/L on day 6. Overall, the microplastic mass release has a downward trend pattern. High microplastic release on day 1 has a mass concentration of 19.000 mg/L, then decreases sharply at 2.333 mg/L on day 4, followed by a stabilization phase at low concentrations (2.000 - 0.500 mg/L). The total accumulated microplastic release during the study period reached 45.333 mg or 55.967% of the total input. These findings indicate that slow-release fertilizer coating contributes significantly to microplastic pollution in aquatic ecosystems.